Students of different manners in higher educational institutions and methods of developing their spiritual moral qualities (Eurasian Scientific Herald, 2023)
In this article, the methods of further improving the moral and ethical qualities in students of different manners who are studying at a higher educational institution, as well as the manifestation of their spiritual qualities in social relations were highlighted.